Studi numerik kekuatan material transmisi roda gigi pico hydro - Akhmad Nurdin; Dwi Aries Himawanto (Jurnal Teknik Mesin Indonesia, 2019)
The generator generate optimum electrical energy if drive system sends the power from turbine to generator with the direction of rotation and speed as needed. The object of this research, how to design spur gear transmission apply for pico hydropower. There are several point to design spur gear transmission, i.e. the bending stress and contact stress on the teeth, and shear stress on the shaft. The strength of the tooth and shaft, simulation using by Ansys Workbench 14.5. Materials used to manufacture gears is polyamide 6 and the shaft material is teflon. Furthermore if design allowable the process of manufacture can be begin, and if manufacture finished, carried testing transmission on the pico hydropower prototype. The result of this research are the design spur gear transmission have total gear ratio 1: 2.65 with two pairs of gears each 1:1.73 and 1 : 1.52. Simulate using by Anys Workbench 14.5 shows the value maximum bending stress 6,1453 MPa on the gear driven first mate, the contact stress 15,415 MPa on the gears driving first mate, and shear stress 1,7688 MPa on the output shaft. Experimental test show the gear transmission produce electric power higher than the electric power produced by direct transmission.